2000
DOI: 10.1046/j.1439-0434.2000.00467.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Trichoderma Isolates from Philippine Rice Fields by UP‐PCR and rDNA‐ITS1 Analysis: Identification of UP‐PCR Markers

Abstract: Forty‐two isolates of Trichoderma from rice fields in four provinces in the Philippines were characterized using rDNA‐ITS1 analysis and universally primed polymerase chain reaction (UP‐PCR). Two groups were clearly distinguishable on the basis of length and restriction pattern of the internal transcribed spacer (ITS) region of the ribosomal DNA and UP‐PCR banding profiles using UP primer, L45. The 40 isolates comprising the largest group were very similar with respect to their UP‐PCR banding profiles and were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 25 publications
2
21
0
1
Order By: Relevance
“…UP-PCR analysis is relatively inexpensive compared to other techniques and is an accurate and efficient method to characterize a large number of unknown Rhizoctonia isolates into their respective AG groups and subgroups. The clusters formed by this method largely agreed with the results of well documented ITS sequence analysis (Kuninaga et al 1997, Gonzalez et al 2001, Hsiang and Dean 2001, Toda et al 2005, de la Cerda et al 2007.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…UP-PCR analysis is relatively inexpensive compared to other techniques and is an accurate and efficient method to characterize a large number of unknown Rhizoctonia isolates into their respective AG groups and subgroups. The clusters formed by this method largely agreed with the results of well documented ITS sequence analysis (Kuninaga et al 1997, Gonzalez et al 2001, Hsiang and Dean 2001, Toda et al 2005, de la Cerda et al 2007.…”
Section: Discussionsupporting
confidence: 81%
“…Successful primers were tagged with fluorescent dye 6-FAM to facilitate data collection on the Applied Biosystems 3730 Genetic Analyzer. The primers L45 (59-GTAAAACGACGGCCAGT-39), L15/AS19 (59-GAGGG TGGCGGCTAG-39), AS15 (59-GGCTAAGCGGTCGTTAC-39), and L21(59-GGATCCGAGGGTGGCGGTTCT-39) (Cumagun et al 2000, Lü beck and Lü beck 2005) were tested. The UP-PCR was performed in a PTC-200 thermo-cycler (MJ Research, Ramsey, Minnesota).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…harzianum is probably the genetically most diverse taxon of the genus. Kubicek, M. Lübeck, unpublished data; see also CUMAGUN et al 2000), and Austria (WUSZKOVSKY et al 2003). In this context, it is interesting that the T. harzianum haplotypes found in this study are rare: one (2c) has not been found before.…”
Section: Discussionmentioning
confidence: 98%